فقہی ذخائر میں فتاوٰی قاضی خان کی اہمیت:فقہائے احناف کی آرا کے تناظر میں ایک مطالعہSignificance of Fatawa Qazi Khan in the Collections of Fiqh: An analytical study in the light of the opinions of Hanafi Jurists (Al-Qamar, 2020)
Imam Fakhar ul din Hasan bin Mansoor Aozjandi Farghani al murginani (592) is the most learned jurist of Hanfi school of thought in the 6th century. He is ranked among the few Ashab-e-Tarjih like Imam-e-Hidaya and Imam-e-Shami. According to Ibn-e-Kamal Pasha, Qazi Khan is one of the most distinguished researchers of Fiqh among the seven ranks of jurists. Not only that, Salman Mansoor puri, a great Mufti (Deo Band school of thought) rightly entitles Hasan bin Mansoor as Mujtahid fil Masail [jurist of contemporary issues]. Also he has declared him as Mujtahid while Imam Hidaya and Imam Shami have been considered as Ashab-e-Tarjih.Qazi khan’s work in Fiqh known as Fatawa Qazi khan consists of three volumes. First time, This book was published from Beirut without publishing date still.  This Ftawa has deep impacts on the later Ftawas of Hanfi school of thought. In contrast with other ftawas, which are written in the form of questions answers, Ftawa Qazi khan is compiled according to the pattern of educational volume. It is a comprehensive guideline and primary source for the later Ftawas of Hanfi school of thought. In fact, the Ftawa has been frequently cited in Ftawa Shami as 264 times, Ftawa Rizvia 1570 times, Ftawa Alamgiri 2776 times and many more in other latest Ftawas like as Ahsan ulfatawa,Fatawa Rashedia , Fatawwa Usmani, Fatawa TatarKhania ,Fatawa Fareedia etc which clearly manifests its worth and prestige. Despite being the primary source for the above mentioned prominent Ftawas, Ftawa Qazi Khan is the least known to the public in common. In the true sense the Ftawa is an encyclopedia for the students of Fiqh. Therefore, this article precisely highlights the life and significant work of Qazi Khan. This research focuses on his modern approach to solve ambiguities in social life in the light of Islamic jurisprudence. The researcher has used descriptive research methodology in this piece of literature to discover the desired outcomes.
Keywords: Fatawa Qazi Khan; Significance; Collections of Fiqh; analytical study; Hanafi Jurists